Strategic Alliance between PT Dirgantara Indonesia and Airbus Millitary (A Case Study of PT Dirgantara Indonesia) - Indriyanto, Reza Relen; Wandebori, Harimukti; Astuti, Novika Candra (The Indonesian Journal of Business Administration, 2013)
PT Dirgantara Indonesia (PT DI) is one of the aircraft manufacturing companies in Indonesia. The tight of competition in aerospace industry needs to improve its performance to gain niche market. Therefore, Ministry State of Own Enterprises has instructed PT Perusahaan Pengelola Aset (PT PPA) and PT DI to restructure and revitalize company with supported by Airbus Military as a strategic alliance partner, in order to increase the performance of production capacity, aircraft sales, and financial. This study focuses on the lifecycle of strategic alliance between PT DI and Airbus Military that consists of planning, formation, operation and termination phase. Strategic alliance is classified into stakeholder support, matching strategic, cross-culture understanding, initial goals and reason, forms of co-operation, alliance initial agreement, human resource management, organizational arrangement, management control system, internal drivers, and external drivers. We use technic in-depth interview and internal data to analyze the strategic alliance between PT DI and Airbus Military. The life cycle of strategic alliance within one and half years between PT DI and Airbus Military includes planning phase, formation phase, and operation phase. After identifying the life cycle of strategic alliance phases, PT DI should improve performance and take benefits from this strategic alliance. Strategic alliance agreement between PT DI and Airbus Military is joint operation or non-equity alliance. It is expected to evolve become equity alliance that requires share of ownership among parties. This study provides strategic alliance evolution that requires company to place trust and commitment, organizational, society, technological, and financial. The result gives contributions for the strategic alliance theory especially in alliance evolution.Â Keywords: strategic alliance, aircraft manufacturing, alliance evolution